2021
DOI: 10.3390/vetsci8020014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Snake Envenomation in Dogs in Queensland, Australia

Abstract: Australia has some of the most venous snakes in the world, and envenomations of domestic dogs are common, but clinical signs as well as the diagnostic procedures and treatments of snake envenomations are poorly described. Therefore, we invited veterinary clinics in the state of Queensland, Australia, to provide detailed data on snake envenomation cases in dogs. A total of 230 cases were reported from 19 veterinary hospitals, with an average of 12.1 dogs per clinic, per year. Detailed case data were provided fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Clinical signs typically are acute in onset (often within 1 h) but can be biphasic or delayed. Retrospective studies report the majority of envenomated patients are presented for veterinary assessment within 6 h (dogs) to 3 days (cats) ( 33 , 36 ). The incidence of dogs and cats that are asymptomatic on presentation is unknown.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Clinical signs typically are acute in onset (often within 1 h) but can be biphasic or delayed. Retrospective studies report the majority of envenomated patients are presented for veterinary assessment within 6 h (dogs) to 3 days (cats) ( 33 , 36 ). The incidence of dogs and cats that are asymptomatic on presentation is unknown.…”
Section: Pathophysiologymentioning
confidence: 99%
“…A retrospective study on hospital admissions in Cyprus due to snake envenomation reported a number of morbidities and two mortality cases [ 24 ]. A retrospective study on snake envenomation in dogs reported collapse, paresis and death as effects of snake envenomation in dogs [ 25 ]. A similar study in Korea reported echinocytosis, anemia and acute kidney injury in dogs that suffered from snake envenomation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%